2021
DOI: 10.35622/j.rie.2021.01.001.es
|View full text |Cite
|
Sign up to set email alerts
|

La gamificación como respuesta desafiante para motivar las clases en educación secundaria en el contexto de COVID-19

Abstract: El objetivo fue determinar la correlación entre la gamificación y la motivación. Se desarrolló mediante la investigación cuantitativa, no experimental y correlacional. Se trabajó con una población censal de 253 estudiantes de educación básica regular. Para la obtención de datos se aplicó la Guía de observación de gamificación de García (2020) y el Cuestionario de motivación MSLQ de T. García et al. (1988). Los resultados indicaron que existe una relación muy baja, significativa de 0.025 (valor de p = 0.0694 &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
1
1
0
3
Order By: Relevance
“…The aforementioned in the previous paragraph is corroborated by the study de Soto significant difference between the groups where conventional instruction and gamified instruction was used furthermore they found in all the sub-dimensions ( p> 0.05) determining that there was no statistically significant relationship; in this picture Villarroel et al (2021) in a correlational study with students in Peru found that the results indicated that there was a very low, significant relationship of 0.025 (p value = 0.0694 > 0.05) so I conclude that gamification is not significantly related to improving student motivation. A factor for the mentioned results is that the teachers were just using some digital tools in a forced way by the context of the COVID-19 pandemic, although these positions have their support in the mentioned studies, the results of this study allow to support that the update of the gamification tools, as well as the context can influence the development of the motivation of the students because after carrying out the intervention the motivation was transformed considerably achieving a 69.2% in the high motivational level, also the satisfaction dimension achieved 79.4% in the high level and the confidence dimension achieved 73.7% in the high level.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The aforementioned in the previous paragraph is corroborated by the study de Soto significant difference between the groups where conventional instruction and gamified instruction was used furthermore they found in all the sub-dimensions ( p> 0.05) determining that there was no statistically significant relationship; in this picture Villarroel et al (2021) in a correlational study with students in Peru found that the results indicated that there was a very low, significant relationship of 0.025 (p value = 0.0694 > 0.05) so I conclude that gamification is not significantly related to improving student motivation. A factor for the mentioned results is that the teachers were just using some digital tools in a forced way by the context of the COVID-19 pandemic, although these positions have their support in the mentioned studies, the results of this study allow to support that the update of the gamification tools, as well as the context can influence the development of the motivation of the students because after carrying out the intervention the motivation was transformed considerably achieving a 69.2% in the high motivational level, also the satisfaction dimension achieved 79.4% in the high level and the confidence dimension achieved 73.7% in the high level.…”
Section: Discussionsupporting
confidence: 57%
“…On the contrary, studies by Mee Mee et al (2020), Yasar et al (2020, Aras and Ciftci (2021) and Villarroel et al (2021) pointed out that gamification is not significantly related to improve motivation, because its use could increase anxiety and jealousy among students, besides teachers are just using some digital tools in a forced way due to the context of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…El qué, con quién, dónde y cuándo debe derivarse de la observación, el enfoque cambia las interacciones entre las personas en el centro (proveedores y pacientes, proveedores y entre sí, pacientes y entre sí) (Dohms et al, 2021). Esto no es solo un cuestionario, más bien, es un conjunto de categorías/temas para guiar el proceso de observación (Villarroel et al, 2021). En particular, fenómenos como comportamientos tabúes o eventos raros son difíciles de capturar (Mendoza Vara, 2018).…”
Section: Methodsunclassified
“…En este mismo contexto, el impacto de la pandemia Covid-19 sobre la educación escolar en general fue significativo, si se considera la digitalización de contenidos y la sustitución de la presencialidad por clases sincrónicas en un aula virtual, usando distintas plataformas y medios para enviar material de lectura, entre otras soluciones que no se pueden considerar como las mejores alternativas de realizar una clase en línea (García-Peñalvo et al, 2020). Lo antes descrito supuso pasar abruptamente de una enseñanza tradicional (esencialmente presencial) a una enseñanza en modalidad virtual, donde la adaptación al cambio presentó dificultades en los docentes para implementar herramientas digitales y el uso de las redes sociales como estrategia de apoyo para poder abordar las clases a distancia (Villarroel et al, 2021). De tal modo que el objetivo de la presente investigación fue conocer la percepción de los profesores de EF de establecimientos escolares sobre el desarrollo de las clases online en el contexto chileno.…”
Section: Introductionunclassified